2016
DOI: 10.1111/jnu.12202
|View full text |Cite
|
Sign up to set email alerts
|

Girlhood Betrayals of Women Childhood Trauma Survivors in Treatment for Addiction

Abstract: Interventions for child and adolescent trauma survivors are critical to prevent the life-long health sequelae of childhood trauma. Pivotal times to engage these survivors include periods when they may be accessed in school and healthcare settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Consistent with previous research, these participants identified multiple forms of emotional and physical interpersonal trauma (IPT) experiences throughout their life. 3 , 28 , 29 , 41–44 This is noteworthy, as IPT is considered among the most detrimental forms of trauma and is associated with increased somatic symptom severity, SUD, suicide risk, and overdose. 45–49 IPT victims are at higher risk for experiencing cumulative trauma and re-victimization, increasing the probability of additional substance issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous research, these participants identified multiple forms of emotional and physical interpersonal trauma (IPT) experiences throughout their life. 3 , 28 , 29 , 41–44 This is noteworthy, as IPT is considered among the most detrimental forms of trauma and is associated with increased somatic symptom severity, SUD, suicide risk, and overdose. 45–49 IPT victims are at higher risk for experiencing cumulative trauma and re-victimization, increasing the probability of additional substance issues.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the content of EW output can provide valuable insight, particularly into women with SUD. Treatment-seeking women with SUD who report trauma histories also report high rates of depression, 26 , 27 guilt and blame, 28 , 29 disruption of intergenerational family dynamics, 26 and transgenerational patterns of trauma. 30 This study provided a unique opportunity to explore these factors through the women's voices and analyze EW content that was not written with the intention of providing researchers with qualitative data; rather, was intended to help facilitate processing.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the subjective nature of traumatic experiences introduces opportunities for further research, given that the way a person responds to and makes sense of the event(s) can shape the leader they become (Bennis & Thomas, 2007). From the literature, we learned that trauma might affect the mental health, self-esteem, and emotional state of Latinas and women overall (Bright & Bowland, 2008;Brunet et al, 2001;Edelson et al, 2007;Grabbe et al, 2016;Moreno, 2007;Neville et al, 2004;Silva-Martínez, 2016); still, researchers have yet to uncover how Latinas, despite the adverse effects of trauma, have attained an executive leadership position and have managed the stressors of a highly demanding career. Many studies on Latina/os leaders have been grounded in Critical Race Theory (Cabello, 2018;Conde-Brooks, 2020;Pertuz, 2017;Rivera, 2019;Savala, 2014) or Latina/o Critical Race Theory, in combination with other concepts (Escobar, 2019;Pertuz, 2017;Rivera, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cultural beliefs such as luck, or suerte, create a fatalistic attitude among Latinas who believe they are powerless and lack control over their lives and future (Moreno, 2007). Lastly, like other studies on women with a traumatic history, Latinas are often sexually abused by multiple individuals, most commonly family members (Bright & Bowland, 2008;Grabbe et al, 2016;Moreno, 2007).…”
Section: The Intersection Of Trauma Gender Ethnicity and Leadershipmentioning
confidence: 98%
See 1 more Smart Citation